The measurement of risk - J. L.R. Retief; W. D. Hamman; J. F. Affleck-Graves (South African Journal of Business Management, 1984)
Risk has so permeated the financial community that no one needs to be convinced of the necessity of including risk in investment analysis. Although the accounting profession has accepted that the purpose of accounting is to facilitate decision-making, implementation of this approach within financial-statement preparation has been impeded by an inability to specify the decision processes of external users of accounting data. Past research, however, provides some empirical knowledge of the decision processes of the investor in a company's shares. This study extends that research in terms of its implications for accounting. The accounting system generates information on several relationships considered by many to be measures of risk. Previous research suggests that financial-statement ratios can be used as measures of default risk, but little is known of their association with risk as defined by the beta coefficient in the capital asset pricing model, generally known as the market model. The problem is compounded by the fact that the capital asset pricing model specifies its risk measures solely in terms of market interactions (i.e. share price variables). An important Issue is the relationship between the accounting-determined and market-determined measures of risk. This article investigates this relationship, utilizing a sample of companies from the Johannesburg Stock Exchange, and compares results with those of similar studies conducted in the USA.
Keywords: 650